El meandro de la Peña el Cuervo: un ejemplo de dinámica fluvial actual del Bajo Gállego (Depresión del Ebro) - Peña Monné, José Luis; Rubio Fernández, Virginia; Longares Aladrén, Luis Alberto; Sánchez Fabre, Miguel (Geographicalia, 2014)
During the last decades transformations due to human action have caused significant changes in the lower Gállego River fluvial dynamics. As a testimony to its nowadays running, we analyze one meander of this river reach during the 2003-2004 floods, when its mixed behaviour was clearly seen. On one hand, while flooded this river is able to build lobed and transverse bars with trajectory and development quite close to a braided system. On the other hand, when the flow decreases, it generates bar breaks that supply the formation of point-barsand consent the recovery of the usual meandering course. This alternating dynamic is responsible of subsequent irregularities in the slope withrapids that are sometimes enhanced by changes in the resistance of the substratum, which is accessible by the river as a consequence of recent incision processes.
Keywords: Gállego River; fluvial dynamics; fluvial bars; incision.